Genetics and Evolution of Abiotic Stress Tolerance in Plants - Galeffi, Patrizia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint represents a general view of what and how the research on plants at the molecular level (genetics, genomics, transcriptomics, proteomics, metabolomics, and so on) contributes to a good equilibrium among human needs, food security, and future strategies for mitigating the effects of global climate changes. Now more than ever, it is critical to understand the genetics and evolution of the gene mechanisms and the networks of different molecular pathways acting on plant abiotic stress tolerance in order to find new solutions for modern agricultural problems.This reprint is full of technical and specialized terms and, for this reason, its target audience is scientists and students trained in plant functional genomics, breeding, agronomy, and genetics. It is an exciting virtual tour through plant molecular responses to various environmental stresses, and new ideas and applications will be derived.